Penanganan penyu yang tertangkap rawai tuna di Samudera Hindia - Budi Nugraha; Irwan Jatmiko; Hety Hartaty (Depik, 2017)
Turtle is one of the vulnerable of megafauna and as a by-catch in tuna longline fisheries, however, management practices have not been done yet. This paper described the efforts to avoid the capture of turtles on the tuna longline fishery and its handling recommendation. It has been written based on the research results and observer programs of activities that have been implemented since 2005. Its also including a literature review rules and regulations regarding the management of sea turtles. The record results during 2005 - 2014 conducted by an independent scientific board on tuna longline in the Indian Ocean with 72 times number of setting and 89,441number of hooks. There are 105 turtles caught, which are leatherback, olive ridley turtles, hawksbill, loggerhead sea turtles as well as the unknown green turtle where the current status of turtles in the Indian Ocean is in a state of vulnerable, endangered, critically even endangered. The olive ridley turtle, loggerhead and leatherback turtles are in a vulnerable status. While, the green turtles are in a state endangered and even hawksbill in a state extremely endangered. Policy measures for handling of turtles in tuna longline fishery needs to be taken in order to be implemented include the socialization of the use of intensified circle hooks and if necessary the government issued regulations regarding the use of circle hooks, the implementation of the placement of fishing monitoring (observer) aboard the tuna longline in order to assist the skippers monitoring the catch of turtles and turtle handling training for the skippers and crew in order to hold the caught turtles can be handled directly on the boat to reduce the mortality turtles which can be released back into the sea alive.Penyu merupakan salah satu biota yang rawan punah dan sebagai hasil tangkapan sampingan pada perikanan rawai tuna dimana pengelolaannya belum banyak dilakukan. Makalah ini membahas tentang upaya bagaimana menghindari tertangkapnya penyu dan rekomendasi penanganan penyu pada perikanan rawai tuna. Tulisan disusun berdasarkan penelusuran hasil penelitian maupun kegiatan program observer yang telah dilaksanakan sejak tahun 2005, dilengkapi kajian pustaka serta peraturan terkait pengelolaan penyu. Hasil pencatatan selama periode 2005 2014 yang dilakukan oleh pemantau ilmiah di kapal rawai tuna di Samudera Hindia dengan jumlah setting sebanyak 72 kali dan 89.441 buah pancing tertangkap 105 ekor penyu, yang terdiri dari penyu belimbing, penyu lekang, penyu sisik, penyu tempayan dan penyu hijau serta penyu yang tidak diketahui jenisnya dimana saat ini status penyu di Samudera Hindia berada dalam kondisi rentan, terancam punah bahkan sangat terancam punah. Penyu lekang, penyu tempayan dan penyu belimbing berada dalam status rentan. Sementara penyu hijau berada dalam keadaan terancam punah dan bahkan penyu sisik berada dalam keadaan sangat terancam punah. Langkah-langkah kebijakan penanganan penyu pada perikanan rawai tuna yang perlu dilaksanakan adalah mengintensifkan penggunaan pancing lingkar, perlu regulasi penggunaan pancing lingkar, implementasi penempatan pemantau penangkapan ikan (observer) di atas kapal rawai tuna agar dapat membantu para nahkoda memonitoring hasil tangkapan penyu dan pelatihan penanganan penyu bagi para nahkoda maupun anak buah kapal yang bertujuan agar penyu-penyu yang tertangkap dapat ditangani secara langsung di atas kapal sehingga menurunkan tingkat kematian penyu-penyu tersebut kemudian dapat dilepas kembali ke laut dalam kondisi hidup.